Intramolecular charge transfer of a push–pull chromophore with restricted internal rotation of an electron donor. Issue 10 (23rd February 2022) - Lee, Sebok; Jen, Myungsam; Lee, Gisang; Jang, Taehyung; Pang, Yoonsoo
Abstract : A push–pull chromophore LD688 with hindered internal rotation of the dimethylamino group occurs via twisting of the julolidine moiety with intramolecular charge transfer. Abstract : Intramolecular charge transfer (ICT) of 4-(dicyanomethylene)-2-methyl-6-[2-(2, 3, 6, 7-tetrahydro-1 H, 5 H -benzo[ ij ]quinolizin-9-yl)vinyl]-4 H -pyran (LD688) in DMSO solution was investigated by femtosecond stimulated Raman spectroscopy (FSRS) with 403 nm excitation. The molecular structure of LD688 is similar to that of a well-known push–pull chromophore, 4-dicyanomethylene-2-methyl-6-( p -dimethylaminostyryl)-4 H -pyran (DCM), except that the internal rotation of the electron-donating dimethylamino group is restricted with the introduction of the julolidine moiety. Upon photo-excitation, LD688 shows an ultrafast (1.0 ps) ICT followed by the vibrational relaxation (3–8 ps) in the charge-transfer (CT) state. Two distinct Raman spectra of LD688 in the locally excited (LE) and CT state of the S1 state were retrieved from FSRS measurements. Based on the time-dependent density functional theory (TDDFT) simulations, a "twisted" julolidine geometry of LD688 was proposed for the ICT state, which was further confirmed in comparison to the spectral changes of several push–pull chromophores with the π-conjugated backbone of stilbene, biphenyl, styrylpyran, styrylpyridinium, and styrene in terms of the skeletal vibrational modes of ν 19b, py, ν CC, ph, and ν CN .